Christian footings creation, world religions, personalism, Revelation, and Jesus - Imperato, Robert, 1945- (University Press of America, 2009)
"Roberto Iperato looks at the question of the relationship between Christianity and world religions to discover what is specifically developed within Christianity. The two concepts that emerge are Person and Word. This text will introduce students to the writings of such key Catholic authors as Teilhard, Merton, Balthasar, Panikkar, Schillebeeckz, and others ..."--P. [4], cover.